The Use of Mannan-Oligosaccharides and/or Tannin in Broiler Diets - McCann, M.; Newell, E.; Preston, C.; Forbes, K. (International Journal of Poultry Science, 2006)
Mannan-oligosaccharides (MOS) and tannin have been reported to have possible growth promoting properties and to possess properties which may control coccidiosis. A total of 300 broilers were divided into 15 groups of 20 birds (at day 1) and three groups of 20 birds were assigned to each dietary treatment. Treatment 1 was a negative control, basal diet, and MOS (SAF-Mannan, Lesaffre, 0.5 g/kg), tannin (condensed chestnut tannin, 0.5 g/kg) and MOS/tannin (0.5 and 0.5 g/kg respectively) were added to the basal diet to produce Treatments 2, 3 and 4. Treatment 5 was a positive control and contained the antibiotic growth promoter, avilamycin (Maxus®, Elanco). Birds assigned to Treatment 5 also received a commercial vaccine, BayCox 2.5% oral solution, in the drinking water (1 ml/litre) (positive control). Average daily gain, feed intake and feed conversion efficiency were determined weekly for 35 days. The birds were challenged with coccidiosis on day 28 by oral administration of a solution containing sporulated oocysts of Eimeria acervulina, Eimeria tenella and Eimeria maxima. On day 35, birds were slaughtered and dissected and assessed for lesion scores at a number of regions along the intestinal tract. Neither MOS or tannin were effective in improving performance to a level comparable to that achieved with the use of the antibiotic growth promoter. The challenge with coccidiosis was successful, with birds across the treatments showing reduced growth on the subsequent seven days after infection. Supplementation of MOS or tannin either individually or in combination did not reduce the impact of coccidiosis. Chi-squared analysis of the intestinal lesion scores indicated that there was a significant effect of treatment, but it was not clear whether MOS or tannin offered a protective effect against coccidiosis.